2019
DOI: 10.3390/molecules24224110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Resins Using Epoxies and Humins as Building Blocks: A Mechanistic Study Based on In-Situ FT-IR and NMR Spectroscopies

Abstract: The combination of eco-respectful epoxy compounds with the humins, a by-product of biomass chemical conversion technologies, allow the obtention of materials with high added value. In this work, we propose a chemical connection study of humins with two aliphatic bis-epoxides through copolymerization reactions to synthesize sustainable, bio-based thermosets. The mechanism insights for the crosslinking between the epoxides and humins was proposed considering the different functionalities of the humins structure.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(58 reference statements)
0
9
0
1
Order By: Relevance
“…Consequently, this behaviour limits their use in many industrial applications. The group of Mija has overcome this limitation by combining humins with epoxide based aliphatic ethers, as a toughening approach, resulting in humins copolymers that have a ductile and elastomeric character [ 92 , 93 , 94 ]. A recent publication discusses the use of humins as a biobased binder in asphalt as a partial replacement of bitumen [ 95 , 96 ].…”
Section: How the Technologies Developed Over Timementioning
confidence: 99%
“…Consequently, this behaviour limits their use in many industrial applications. The group of Mija has overcome this limitation by combining humins with epoxide based aliphatic ethers, as a toughening approach, resulting in humins copolymers that have a ductile and elastomeric character [ 92 , 93 , 94 ]. A recent publication discusses the use of humins as a biobased binder in asphalt as a partial replacement of bitumen [ 95 , 96 ].…”
Section: How the Technologies Developed Over Timementioning
confidence: 99%
“…Especially this aspect has challenged our previous work and studies for developing proper strategies for the humins-based materials design. Based on intense and thorough studies, [28][29][30][31] we found that copolymerization of humins with different epoxides generate materials with modulated mechanical properties from elastic to rigid, with a long lifespan, their physico-chemical and mechanical characteristics remaining optimal over time. The use of humins in large quantities (55 wt.%), the use of renewable, cheap, and industrially available co-reactants, the development of materials through cost competitive processes, but especially the tailoring of rigid furan materials with competitive thermo-mechanical properties for various industrial sector, made the resin used for this study a good candidate for testing the influence of humins composition on the final properties of the resulting materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the epoxidized linseed oil (ELO) has been selected due to its high functionality (~5.5 epoxy groups/triglyceride) and the large accessibility of linseed crops in Europe. In the last years many efforts have been focused on sustainable synthesis of ELO based thermosets [26,27,30]. Another, biomolecules that are attracting plenty of attraction are sugars [31] or biopolymers such as cellulose [32] and lignin [33], due to their properties and chemical structures these natural compounds can be used as raw materials for the fabrication of matrices.…”
Section: Introductionmentioning
confidence: 99%